PENDAMPINGAN KONTEN KREATIF DAKWAH DIGITAL DI PONDOK PESANTREN RIYADLATUL ULUM LAMPUNG TIMUR - Anton Widodo; Agam Anantama; Siroy Kurniawa; Mia Nurislamiah (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
The development of digital technology has brought significant changes to communication patterns in society, including the practice of Islamic da‘wah. Da‘wah, which was traditionally delivered through conventional face-to-face methods, has gradually transformed into digital da‘wah that utilizes internet-based media and creative content. Islamic boarding schools (pondok pesantren) as Islamic educational institutions play a strategic role in responding to this transformation, particularly in preparing students (santri) to actively participate in da‘wah activities that are adaptive to the digital era. This study aims to conceptually examine the mentoring of creative digital da‘wah content at Pondok Pesantren Riyadlatul Ulum, East Lampung, as an effort to strengthen Islamic da‘wah in the digital age. The research employs a qualitative approach using a library research method by reviewing and analyzing relevant academic literature, including scholarly journal articles, reference books, and official publications related to digital da‘wah, creative content, digital literacy, and the role of Islamic boarding schools. The findings indicate that mentoring creative digital da‘wah content plays an important role in enhancing students’ digital literacy, creativity, and awareness of ethical media practices. Furthermore, such mentoring contributes to strengthening the institutional capacity of Islamic boarding schools as centers of moderate, contextual, and sustainable digital da‘wah. Therefore, mentoring creative digital da‘wah content can be regarded as a relevant strategy for developing pesantren-based Islamic da‘wah in the contemporary digital era.